Capturing Iraq: Optical Focalization in Contemporary War Cinematography. Issue 4 (19th May 2018) - Fox, Rachel
Abstract : This essay investigates different registers of embedded and fragmentary focalizations in war cinematography on the Iraq War (2003–11), focusing primarily on The Hurt Locker (2008) and the HBO mini-series Generation Kill (2008), but also addressing American Sniper (2014) and the Abu Ghraib scandal. I argue the "extreme close-up" that focuses almost unilaterally on the men on the ground during the Iraq War implicates a "bigger picture": a larger frame of discourse put forward by the corporate media and the government. This is primarily achieved through recursive narrative structures and through the use of diegetic ocular apparatuses, which are embedded on screen. These renditions of mise en abyme implicate, renegotiate, and even argue with the wide-angle perspective which frames the Iraq War.